(untitled) (Indian Journal of Animal Production and Management, 2016)
Data on growth traits of 7161 animals used in present study were collected from the history sheets of Rambouillet sheep maintained at Government Sheep Breeding Farm, Reasi, J&K, India. Growth traits included in the study were birth weight (BW), three-month weight (3MW), six-month body weight (6MW), nine-month body weight (9MW) and twelve-month body weight or yearling weight (YW). The average weight gain of individual during 0-3 months (ADG1), 3-6 months (ADG2), 6-9 months (ADG3), 9-12 months (ADG4) and 3-12 months (ADG5) were calculated as weight gain during particular period divided by duration of that period in days. The overall averages were 3.39±0.01kg, 14.16±0.03kg, 19.59±0.04kg, 24.85±0.05kg and 28.71±0.06kg, respectively for BW, 3MW, 6MW, 9MW and YW. The overall averages were 0.119±0.002kg, 0.071±0.001kg, 0.058±0.006kg, 0.056±0.001kg and 0.054±0.001kg, respectively for ADG1, ADG2, ADG3, ADG4 and ADG5. Sex had significant effect on all growth traits under study except for 9 MW, where sex had non-significant. For growth rate traits sex had non-significant effect for ADG1 and ADG4. The correlation coefficients of between different body weights and average daily weight gain ranges from -0.040±0.01 between ADG1 & ADG5 to 0.97±0.01 between BW and 9W. Most of the correlations values were highly significant barring few exceptions, which indicate improvement of one trait will result in improvement of other traits also. Low to medium coefficient of variations (CV) for growth traits indicate collateral selection will be effective for improvement of growth traits.